A revision of the Juncaceae with delimitation of six new genera: nomenclatural changes in Juncus - Proćków, Jarosław; Drábková, Lenka Záveská (Phytotaxa, 2023)
Phylogenetic relationships within the genus Juncus L. remained poorly understood for most groups, and the taxonomic division to two subgenera and ten sections was rather pragmatic. The taxonomic treatment based on the morphology of this group is complicated due to numerous repeated reductions. Continuing the molecular phylogenetic, taxonomic, and nomenclatural studies of the Juncaceae, we propose a nomenclatural revision of Juncus and propose 379 new combinations for six newly recognized genera based on combined morphological and molecular data support: Verojuncus Záveská Drábková & Proćków, Juncinella (Fourr. ex V.I.Krecz. & Gontsch.) Záveská Drábková & Proćków, Alpinojuncus Záveská Drábková & Proćków, Australojuncus Záveská Drábková & Proćków, Boreojuncus Záveská Drábková & Proćków, and Agathryon (Raf.) Záveská Drábková & Proćków.